A Descriptive Study on Cultural Impact On Celebrating Festivals Of India - et. al., Ms. Lekha Fenn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Festivals In India Is Regarded As Most Significant Occasion Celebrated By People As Part Of Their Culture. Especially In India Ignoring Region, Religion, Caste And Creed They Celebrate The Festivals With Togetherness In Joy And Happiness. The Celebration Leads To Get Together Of Families, Friends And Neighbours To Come Out From Monotonous Lifestyle And Share Joy And Peace. India Is Known For Its High Cultural Heritage, In This Article The Author Attempt To Establish The Cultural Impact On Celebrating Festivals Of India By Demonstrating The Relationship Between Culture And Festivals, Culture In Human Values And Understanding Indian Festivals.